Strain induced effects in p-type silicon whiskers at low temperatures - Druzhinin, A.A.; Maryamova, I.I.; Kutrakov, O.P.; Liakh-Kaguy, N.S.; Palewski, T. (Functional Materials, 2012)
Complex studies of strain induced effects in boron doped p-type silicon whiskers with [111] crystallographic direction in the wide temperature range 4.2 - 300 K at magnetic fields up to 14 T and under high-energy electron irradiation were carried out. The peculiarities of piezomagnetoresistance of Si whiskers heavily boron doped and with boron concentration in the vicinity of metal-insulator transition were determined. The influence of electron irradiation with energy 10 MeV and fluence Φ = 5*10¹⁷ el/cm ² on the gauge factor of boron doped Si whiskers at low temperatures have been also studied. High-sensitive piezoresistive sensor to measure pressure of liquid helium on the basis of silicon whiskers with a giant gauge factor was developed. Heavily doped Si whiskers with classic piezoresistance have been successfully used in mechanical sensors operating in the wide temperature range 4.2 - 300 K.